PELATIHAN BAHASA INGGRIS PRAKTIS UNTUK TOUR LEADER DI PT. SHIRO MANDIRI WISATA DALAM MENGUASAI TEKNIK PEMANDUAN WISATA MENGGUNAKAN BAHASA INGGRIS - Zuraida , Ida; Heryono, Heri; Hendar, Hendar; Astarina, Atri Nadia; Sujatna, Meita (LPPM Universitas Bina Bangsa, 2025)
Practical English Training for Tour Leaders organized by the English Study Program of Widyatama University at PT. Shiro Mandiri Wisata aims to improve English communication skills for tour leaders. This study aims to evaluate the effectiveness of the training based on aspects of the suitability of the material, the skills mastered, and the frequency of English use in work. The method used involved a survey through a questionnaire filled out by the training participants. The results showed that 71% of participants felt that the training material was very appropriate for their needs. The most widely mastered skill was writing (38.1%), while the frequency of English use in work was still relatively low, with 54% of participants stating that they rarely used it. These findings indicate that although the training provides benefits in improving English comprehension, further efforts are still needed to improve speaking and listening skills, as well as improve the application of English in the work environment. Recommendations provided include increasing speaking practice, implementing English use policies in the company, and providing further training and certification programs. With these steps, it is hoped that tour leaders can be more confident and competent in providing tour guide services for foreign tourists.